Metaretorika Dakwah: Analisis Ceramah ‘Rutinan Malam Selasa’ Gus Iqdam - Hakim, Lukman; Mukhlis, Zainal; Pardianto (Jurnal Komunikasi Islam, 2025)
This study explores the metarhetoric KH Muhammad Iqdam Kholid's, known as Gus Iqdam, sermons in "Rutinan malam Selasa". Through qualitative text analysis, the study reveals that his use of classical rhetorical elements—ethos, pathos, and logos—is strategically developed to help the audience grasp religious teachings logically while fostering a sense of connection with the audience. Gus Iqdam employs deductive, causal, and comparative reasoning not only to convey religious messages but also to demonstrate their rational basis. His pathos-based metarhetoric is expressed at times through emotionally charged spiritual appeals. Meanwhile, his ethos-driven metarhetoric serves to establish credibility and encourage emotional, intellectual, and spiritual trust from the congregation.